Liver injury in hospitalized patients with COVID-19: an international observational cohort study - Tirupakuzhi Vijayaraghavan, BK; Bishnu, S; Baruch, J; Citarella, BW; Kartsonaki, C; Meeyai, A; Mohamed, Z; Ohshimo, S; Lefèvre, B; Al-Fares, A; Calvache, JA; Taccone, FS; et al. (Public Library of Science, 2023)
Background Using a large dataset, we evaluated prevalence and severity of alterations in liver enzymes in COVID-19 and association with patient-centred outcomes.